Choniomyzon libiniae, sp. n. (Crustacea, Copepoda, Nicothoidae) from S o Sebasti o, SP, Brazil - Santos, Cynthia; Björnberg, Tagea (Zootaxa, 2004)
A new nicothoid (Choniomyzon libiniae Santos and Bj rnberg, new species) was found on the eggs of the decapod crustacean Libinia spinosa collected at Anchovas Beach (S o Sebasti o Island, SP, Brazil). The material obtained was fixed in formalin, cleared in lactic acid and glycerin, and the different forms of the parasite were drawn with the aid of a microscope and a camera lucida. The parasite eggs were attached to the host’s eggs. Nauplii, three forms of copepodids, and adult females and males were found. The 12-segmented first antennae, the segmented urosome, the long and branched caudal setae, the oval form of the female, the lecithotrophic nauplius, a copepodid similar to the one described for Choniomyzon permitted the inclusion in this genus. It differs from the species described (C. panuliri Pillai) by the ornaments of the antenna and of the female legs, also by the presence of three types of copepodids.